LARGE THALLIUM ISOTOPIC VARIATIONS IN IRON METEORITES AND EVIDENCE FOR LEAD-205 IN THE EARLY SOLAR SYSTEM - Nielsen S.G.; Rehk?mper M.; Halliday A.N. (My University, 2006)
Lead-205 decays to 205Tl with a half-life of 15 Myr and should have been present in the early solar system according to astrophysical models. However, despite numerous attempts, Tl isotopic measurements of meteorites have been unable to demonstrate convincingly its former presence. Here, we report large (?5?) variations in Tl isotope composition in metal and troilite fragments from a range of iron meteorites that were determined at high precision using multiple collector inductively coupled plasma mass spectrometry. The Tl isotopic compositions of seven metal samples of the IAB iron meteorites Toluca and Canyon Diablo define a correlation with 204Pb/203Tl. When interpreted as an isochron, this corresponds to an initial 205Pb/204Pb ratio of (7.4 ? 1.0) ? 10-5. Alternative explanations for the correlation, such as mixing of variably mass-fractionated meteorite components or terrestrial contamination are harder to reconcile with independent constraints. However, troilite nodules from Toluca and Canyon Diablo contain Tl that is significantly less radiogenic than co-existing metal with isotope compositions that are variable and decoupled from 204Pb/203Tl. These effects are similar to those recently reported by others for Fe and Ni isotopes in iron meteorite sulfides and appear to be the result of kinetic stable isotope fractionation during diffusion. Though it cannot conclusively be shown that the metal fragments are unaffected by the secondary processes that disturbed the troilites, mass balance modeling indicates that the alteration of the troilites is unlikely to have significantly affected the Tl isotope compositions of the co-existing metals. It is therefore reasonable to conclude that the IAB metal isochron is a product of the in situ decay of 205Pb. If the I-Xe ages of IAB silicate inclusions record the same event as the 205Pb-205Tl chronometer then crystallization of the IAB metal was probably completed between 10 and 20 Myr after the condensation of the first solids. This implies an initial solar system 205Pb/204Pb of (1.0-2.1) ? 10-4, which is in excellent agreement with recently published astrophysical predictions. Similar calculations yield an initial solar system Tl isotope composition of ?205Tl = -2.8 ? 1.7. The Tl isotopic composition and concentration of the silicate Earth depends critically on the timing and mechanism of core formation and Earth’s volatile element depletion history. Modeling of the Earth’s accretion and core formation using the calculated initial solar system Tl isotope composition and 205Pb/204Pb, however, does not yield reasonable results for the silicate Earth unless either the Earth lost Tl and Pb late in its accretion history or the core contains much higher concentrations of Pb and Tl than are found in iron meteorites. ? 2006 Elsevier Inc. All rights reserved.
Keywords: IRON METEORITE; ISOTOPIC COMPOSITION; LEAD ISOTOPE; SOLAR SYSTEM; THALLIUM; TOLUCA